Mathematical Methods of Organizing and Planning Production - Kantorovich, L. V. (Management Science, 1960)
The author of the work “Mathematical Methods of Organizing and Planning Production”, Professor L. V. Kantorovich, is an eminent authority in the field of mathematics. This work is interesting from a purely mathematical point of view since it presents an original method, going beyond the limits of classical mathematical analysis, for solving extremal problems. On the other hand, this work also provides an application of mathematical methods to questions of organizing production which merits the serious attention of workers in different branches of industry. This is the English translation of the famous 1939 article by L. V. Kantorovich, originally published in Russian.